TINJAUAN PENGETAHUAN MASYARAKAT KOTA BANDA ACEH TERHADAP OBAT TRADISIONAL - Fauziah; Maisura; Rinaldi (Sekolah Tinggi Ilmu Kesehatan Borneo Lestari Banjarbaru, 2019)
ABSTRACTTraditional medicine is a medicine that comes from nature which is derived from generation to generation and is use based on experience. The use of traditional medicine in the community is very dependent on the knowledge of the community it self, the better the knowledge of the community, the more utilization of traditional medicine. This research aims to find out the knowledge of the city of Banda Aceh on traditional medicine. The scope in this research is limited to traditional medicine in packaging. The research method was carried out descriptively using an instrument in the form of a questionnaire. The research was conducted on June 1 to July 2018 at the city health center in Banda Aceh. This research started The population is the entire adult population of the Banda Aceh amounting to 139.503 people with a sample of 399 respondents taken by quota sampling. The results showed that the knowledge of Banda Aceh on the benefits of traditional madicine was good (78%), knowledge of legality was sufficient (72%), knowledge of adequate doses (74%), knowledge of side effects was enough (74%) with average values 63% of enough categories. So, it can be concluded that the description of the knowledge of the people of the city of banda aceh about traditional medicine is included in the category enough.Keyword: knowledge, traditional medicine, community